Crença dogmática e crença científica na filosofia de Charles Sanders Peirce - Prado, Luiz Adelino de Almeida (2012)
The purpose of the present Master s dissertation is to study the path followed by Peirce in the working up of his concept of belief, from the antecedents that determined it, up to the formulation of the pragmatist maxim. Along this study we shall consider, among other issues, the new role established for the doubt, which for Peirce is the opposite of belief, the importance of the scientific method of fixing belief and Peirce s critique of cartesianism. This critique will also be compared to Kant s critique of dogmatism and skepticism